Tinjauan Hukum Ekonomi Syariah Tentang Jual Beli Barang Yang Sudah Digunakan Dengan Harga Barang Baru (Studi Kasus Di Desa Sukarasa Kecamatan Samarang Kabupaten Garut) - Gausian, Gini; Roviyana, Ai (Jurnal Hukum Ekonomi Syariah, 2023)
According to Sharia economic law, buying and selling is allowed as long as neither party is dzolimi.  But in this sale and purchase there is one party that is harmed, namely the buyer, the goods sold are goods that can be called used goods because they have been used. Sharia Economic Law is certainly not in accordance with its principles, namely there must be principles of honesty and truth. This study aims to describe the sale and purchase of goods that have been used at the price of new goods in terms of the theory that states that buying and selling is Buying and selling is an activity of exchanging goods with property in the form of money. Buying and selling goods that have been used at the price of new goods is a buying and selling activity that only earns profits for the seller. Based on the results of research in the Sharia Economic Law Review, buying and selling goods that have been used at the price of new goods in Sukarasa Village, Samarang District, Garut Regency is said to be valid if the transaction is harmonious and the legal requirements have been met. But if the harmony and legal conditions are not met, such as fraud in the transaction, then the trade is damaged or void.  Keywords: Sharia Economic Law, buying and selling, goods that have been used